District of Columbia Community Health Needs Assessment - Chandra, Anita (RAND Corporation, 2013)
This report guides the District of Columbia Healthy Communities Collaborative's decisions about where and how to allocate resources and implement appropriate health interventions for the population it serves. The community health needs assessment described in this report includes quantitative analysis of existing demographic, health status, and hospital service use data for the District of Columbia, as well as analysis of current stakeholder perspectives, health policy, and investment priorities.